ENVIRONMENTAL UNCERTAINTY, DEBT POLICY, TAX AVOIDANCE: DOES MANAGERIAL ABILITY MATTER? - Luthfia Annida; Amrie Firmansyah (Kesatuan Press, 2022)
This study examines the effect of environmental uncertainty and debt policy on tax avoidance. In addition, this study also examines managerial ability as a moderating variable in relationship between independent and dependent variables. The method used in this study is quantitative. This study utilizes secondary data from annual financial reports of property & real estate sector companies listed on the Indonesia Stock Exchange from 2018 to 2020. Based on purposive sampling, the total sample of this study amounted to 77 observations. The data derives from www.IDX.co.id and official company website. The analysis technique used is multiple linear regression for the cross-section data. The results of this study suggest that environmental uncertainty is not associated with tax avoidance, while debt policy is negatively associated with tax avoidance and indicates that managerial ability weakens the positive effect of environmental uncertainty on tax avoidance. Meanwhile, the managerial ability does not moderate the relationship between debt policy and tax avoidance. This research indicates that the Indonesia Financial Services Authority needs to supervise listed companies to increase protection for investors in capital market. In addition, the Indonesian Tax Authority needs to improve the income tax policy for corporate taxpayers related to company's capital structure.